ЁШ СПОРТЧИЛАРДА МОТИВАЦИЯНИНГ ЮЗАГА ЧИҚИШИДА ҚАДРИЯТЛАРНИНГ ЎРНИ - Бахромов, О. (SCIENCE and SOCIETY, 2020)
This article discusses the results of a study on the role of values in the formation of motivation in young athletes.